2016
DOI: 10.1007/s10565-016-9327-z
|View full text |Cite
|
Sign up to set email alerts
|

Silencing GTSE-1 expression inhibits proliferation and invasion of hepatocellular carcinoma cells

Abstract: G2 and S phase-expressed-1 (GTSE1) was recently reported to upregulate in several types of human cancer, based on negatively regulate p53 expression. However, its expression and functional roles in hepatocellular carcinoma (HCC) remain unknown. In this study, GTSE1 was observed to be highly expressed in HCC specimens and cell lines both at messenger RNA (mRNA) and protein levels. Furthermore, high GTSE1 expression was positively associated with tumor size, venous invasion, advanced tumor stage, and short overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…GTSE1 regulates the cell cycle by interacting with p53 and repressing its ability to induce apoptosis . Previous studies have investigated the expression and functional mechanisms of GTSE1 with respect to the tumor cell cycle . Consistently, our investigation showed that upregulation of GTSE1 leads to increased G2/M phase in AMC‐1 cells, and GTSE1 depletion decreased G2/M phase in WM2664 cells.…”
Section: Discussionsupporting
confidence: 81%
“…GTSE1 regulates the cell cycle by interacting with p53 and repressing its ability to induce apoptosis . Previous studies have investigated the expression and functional mechanisms of GTSE1 with respect to the tumor cell cycle . Consistently, our investigation showed that upregulation of GTSE1 leads to increased G2/M phase in AMC‐1 cells, and GTSE1 depletion decreased G2/M phase in WM2664 cells.…”
Section: Discussionsupporting
confidence: 81%
“…GTSE1 has been demonstrated as a potential biomarker for poor clinical outcome in several types of cancer [10,13,27]. Previous research suggested GTSE1's functional role in hepatocellular carcinoma (HCC) proliferation, colony formation, invasion, and overall survival [9,13]. In our study, DEGs in GTSE1 knockdown In addition to GTSE1, overexpression of CDC20, PCNA, and MCM has been detected in many types of human cancer [28][29][30].…”
Section: Discussionmentioning
confidence: 64%
“…While in normal condition, GTSE1 is activated by functional p53 binding on the GTSE1 promoter region and encodes GTSE1 protein to cause a delay from G2 to M transition [3,8]. Recent studies revealed that overexpression of GTSE1 contributes to promoting cell proliferation, migration, and invasion in different cancers via translocalizing p53 to the cytoplasm [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also responds to DNA damage and inhibits apoptosis. GTSE1 inhibition significantly decreased tumor growth in vitro and in vivo, and suppressed migration and invasion in vitro [18]. Our co-staining data of GTSE1 and Ki67 revealed that fibrotic regions showed high expression of Ki67 accompanied with GTSE1 overexpression in 90Gy focal irradiated lung tissues (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 87%